Analysis of Train Travel Patterns Case Study of Bogor Double Track Construction - Sukabumi - Ependi, Ahmad; Churniawan, Erifendi (Journal of World Science, 2023)
In this study the aim is to analyze the problem of train travel that occurs with the change from single track to double track as well as changes in the layout of the emplacements, which increase the frequency of passenger and freight train trips. The data used in this study are primary and secondary. Primary data includes existing data on the Bogor-Sukabumi operation pattern obtained by interviewing West Java BTP and KAI employees. Secondary data includes data on train star formation, the type and number of trains, signal service time, and the speed of passenger and freight trains. In the planning of road plots in the Detailed Design of Double Tracks Between Bogor - Cigombong, it is not directly affected by traffic capacity. This is because road plots can be divided into several block plots, which is very different from the single-lane system. To reduce Headway or the same as to increase traffic capacity, simply by adding IB (Intermediate Block) between the distances of AB stations (AB (km) S) in the formula, if 1 (one) IB is installed, then the distance of the road plot is divided by two, if 2 (two) IBs are installed, then the distance of the road plot is divided by three and so on. The analysis  study of operational patterns on the Bogor-Sukabumi line shows that with the plan to increase the frequency of trains and the construction of a double track, there will be a decrease in the Headway from 10.38 to 7.1.